PENDAMPINGAN MANAJEMEN DAN PENGUATAN USAHA PADA TKM GANGSAR DESA KUMENDUNG KECAMATAN REMBANG KABUPATEN REMBANG - Dian Anita Sari; Agus Widodo (Buletin Abdi Masyarakat, 2021)
Kumendung Village is one of the governance areas of the Rembang District, Rembang Regency. There is a lot of potential that can be explored in Kumendung Village, one of which is the Gangsar Independent Workforce (TKM) group. TKM Gangsar group is a group for novice tailors totaling 20 people. In its development, there were several problems with the Gangsar TKM Group. The problems in TKM Gangsar are the limited sewing skills of group members, lack of entrepreneurial motivation, lack of market access, and minimal business management. Programs implemented by the Service Team are sewing training (masks), entrepreneurial motivation training, training and assistance in developing market access as well as business management training and assistance. The outputs of this service are the improvement of sewing skills, the development of market access, the existence of a business label, and a national seminar. Keywords: Dedication, Empowerment, Sewing Training, Business Management.